Overexpression of TwSQS, TwSE, and TwOSC Regulates Celastrol Accumulation in Cambial Meristematic Cells and Dedifferentiated Cells - Song, Yadi; Zhou, Jiawei; Zhang, Yifeng; Zhao, Yujun; Wang, Xiujuan; Hu, Tianyuan; Tong, Yuru; Huang, Luqi; Gao, Wei (Frontiers in Plant Science, 2022)
Squalene synthase (SQS), squalene epoxidase (SE) and oxidosqualene cyclase (OSC) are encoding enzymes in downstream biosynthetic pathway of triterpenoid in plants, but the relationship between three genes and celastrol accumulation in Tripterygium wilfordii (T. wilfordii) still remains unknown. Gene transformation system in plant can be used for fast studying gene function. However, there is no report on application of cambial meristematic cells (CMCs) and dedifferentiated cells (DDCs) in genetic transformation systems. Our aim was to study the effects of individual overexpression of TwSQS, TwSE and TwOSC on terpenoid accumulation and biosynthetic pathway-related gene expression through CMCs and DDCs systems. Overexpression vectors of TwSQS, TwSE and TwOSC were constructed by Gateway technology and transferred into CMCs and DDCs by gene gun. After overexpression, the content of celastrol was significantly increased in CMCs compared with control group. However, there was no significant increment of celastrol in DDCs. Meanwhile, the relative expression levels of TwSQS, TwSE, TwOSC and terpenoid biosynthetic pathway-related genes were detected. The relative expression levels of TwSQS, TwSE and TwOSC were all increased compared with control group in both CMCs and DDCs. While the pathway-related genes displayed different expression trends. Therefore, it was verified in T. wilfordii CMCs that overexpression of TwSQS, TwSE and TwOSC increased celastrol accumulation and had different effects on the expression of related genes in terpenoid biosynthetic pathway, laying a foundation for further elucidating the downstream biosynthetic pathway of celastrol through T. wilfordii CMCs system.